Perspektif Sosiologis Dalam Pengembangan Kurikulum - Elis Kurniawati; Marhamah, Marhamah (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2024)
This research aims to investigate the role of sociological perspectives in curriculum development, focusing on understanding the relationship between individuals and society in an educational context. The research objective involves an in-depth analysis of how sociological aspects can guide curriculum design that is responsive to the dynamics of society. Through a descriptive qualitative approach, the research identifies the sociological assumptions on which curriculum development is based and evaluates their impact on the formation of individuals as members of a thriving society.